Trimelopter cordifolium (Hyacinthaceae subfam. Ornithogaloideae), a new species from South Africa - Martínez-Azorín, Mario; Paonessa, Giacomo; Zaalberg, Bert; Crespo, Manuel B.; Vargas, María Ángeles Alonso (Phytotaxa, 2023)
The study of wild and cultivated material of Trimelopter from the Northern Cape province of South Africa revealed an undescribed species that shows a unique syndrome of morphological characters. We here describe Trimelopter cordifolium based on plants approaching T. psammophorum but differing in its small, cordate, psammophorous leaf, shorter inflorescence and pedicels, smaller flowers and bracts, and more prominently sculptured ovary. We provide a complete morphological description as well as data on ecology and distribution. We also report new data and illustrations of T. psammophorum, which complement its scarce description in the protologue.